143PNOTCH3 expression predicts poor survival in advanced esophageal squamous cell cancers. (24th November 2019) - Pramanik, R; Das, P; Sharma, A; Kumar, S; Bhoriwal, S; Pathy, S; Saraya, A
Abstract: Background: Oesophageal cancer is the sixth leading cause of cancer-related mortality with more than 90% of oesophageal cancer being squamous cell carcinomas (ESCC) in Asian countries. Prognosis of ESCC remains extremely poor and identification of better prognostic factors is an unmet need. Methods: We investigated the immune- histochemical expression of Notch1, Notch2, Notch 3, HES-1 (Hairy enhancer of Split -1) (a downstream transcription factor) and p21 among ESCC and non-tumour controls. Non-tumour controls consisted of diagnostic biopsies of GERD patients in which Barrett's and erosive esophagitis had been ruled out. We also investigated the association of these markers with clinico-pathological features and survival. We included 46 patients of ESCC and 42 controls. IHC markers were performed according to the standard guidelines and analysed with a semi-quantitative H –score (The H score was calculated as: H score= D X I with values ranging from 1-15). Results: The median age was 60 (37-78 years). M:F ratio was 30: 16. 65.2 % were smokers and 19.6 % were tobacco chewers. 38 cases were locally advanced (Stage III) and 8 were metastatic at baseline. Palliative intent therapy was offered to 24 % and definitive therapy to 76%. An ECOG -PS of 1, 2 and 3 was observed in 26, 16 and 4 patients respectively. At a median follow up of 50.67 months, the median overall survival was10.47 mon (range= 8.23-15.1) mon. Using a cut-off score of 7.5 to define positivity, NOTCH 1, 2, 3 as well as p21 were found to be significantly over-expressed in ESCC as compared to normal controls, while there was no difference in Hes1 expression. Location, grade, baseline metastases, duration of symptoms showed no association with NOTCH 1, 2 or 3 positivity. On univariate analysis, male sex, age >60 years, smokers, ECOG-PS>1, Notch 3 H score was found significant. On multivariate analysis, smokers (HR = 3.53, p = 0.013), ECOG-PS>1 (HR = 2.88, p = 0.006) and Notch3 H score (HR = 2.38, p = 0.047) emerged as independent adverse prognostic factors. Conclusions: NOTCH 1, 2 and 3 are highly expressed in ESCC as compared to controls. Notch3 H score is an independent predictor of survival in ESCC and merits evaluation in larger studies. Legal entity responsible for the study: Raja Pramanik. Funding: Intramural Research Fund, Research Section, All India Institute of Medical Sciences, New Delhi. Disclosure: All authors have declared no conflicts of interest.